Electroconductive Nanopatterned Substrates for Enhanced Myogenic Differentiation and Maturation. Issue 1 (18th May 2015) - Yang, Hee Seok; Lee, Bora; Tsui, Jonathan H.; Macadangdang, Jesse; Jang, Seok‐Young; Im, Sung Gap; Kim, Deok‐Ho
Abstract : Electrically conductive materials provide a suitable platform for the in vitro study of excitable cells, such as skeletal muscle cells, due to their inherent conductivity and electroactivity. Here it is demonstrated that bioinspired electroconductive nanopatterned substrates enhance myogenic differentiation and maturation. The topographical cues from the highly aligned collagen bundles that form the extracellular matrix of skeletal muscle tissue are mimicked using nanopatterns created with capillary force lithography. Electron beam deposition is then utilized to conformally coat nanopatterned substrates with a thin layer of either gold or titanium to create electroconductive substrates with well‐defined, large‐area nanotopographical features. C2C12 cells, a myoblast cell line, are cultured for 7 d on substrates and the effects of topography and electrical conductivity on cellular morphology and myogenic differentiation are assessed. It is found that biomimetic nanotopography enhances the formation of aligned myotubes and the addition of an electroconductive coating promotes myogenic differentiation and maturation, as indicated by the upregulation of myogenic regulatory factors Myf5, MyoD, and myogenin ( MyoG ). These results suggest the suitability of electroconductive nanopatterned substrates as a biomimetic platform for the in vitro engineering of skeletal muscle tissue. Abstract : Bioinspired cell culture substrates are developed to enhance myogenic differentiation and maturation. Polyurethane acrylate films nanopatterned using capillary force lithography are coated with a thin layer of titanium or gold with electron beam deposition to create electroconductive substrates with well‐defined nanotopography. These not only induce increased myoblast alignment, but also promote formation of myotubes expressing sarcomeric myosin heavy chain.